1863 [zbiór znaczków podziemnych] . 1863. Set of unofficial stamps - Poczta Solidarności Walczącej. (Poczta Solidarności Walczącej, 1988)
Black and red or blue print on white or silver paper, without perforation. Stamp, with "Poczta Solidarności Walczącej" imprint, issued on the 125 anniversary of the January Uprising in Poland (1863), represents the insurgents lifting a Polish banner. Price: 70 zł per stamp.